2007
DOI: 10.11606/issn.1678-4456.bjvras.2007.26628
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologia da poxvirose bovina no Estado do Espírito Santo, Brasil

Abstract: O trabalho consistiu no estudo epidemiológico do surto de poxvirose bovina no Estado do Espírito Santo no período de 2002 a 2005. A coleta dos dados deu-se em 28 propriedades de gado bovino leiteiro de 08 municípios do Sul do Estado do Espírito Santo com casos de doenças pústulo-vesicular em bovinos, no período de agosto de 2002 a maio de 2005. Observou-se que a prevalência da doença no gado bovino leiteiro variou de 10,2% a 100% das propriedades com média de 52,7%. Através de isolamento viral e PCR do gene Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 9 publications
1
11
0
1
Order By: Relevance
“…In the state of Rio de Janeiro, animal and human poxvirus infections have been repeatedly described along the years (Silva & Moraes 1961, Mesquita & Schatzmayr 1969, De Souza et al 2003, Costa et al 2007, Donatele et al 2007. In this article, the clinical lesions observed in the animals confirmed observations of these authors.…”
Section: Discussionsupporting
confidence: 80%
“…In the state of Rio de Janeiro, animal and human poxvirus infections have been repeatedly described along the years (Silva & Moraes 1961, Mesquita & Schatzmayr 1969, De Souza et al 2003, Costa et al 2007, Donatele et al 2007. In this article, the clinical lesions observed in the animals confirmed observations of these authors.…”
Section: Discussionsupporting
confidence: 80%
“…Other authors have confirmed through the years the presence of animal and human infections with poxvirus, especially in the southeast region (Mello et al 1960, Silva & Moraes 1961, De Souza et al 2003, Donatele et al 2007). …”
Section: Vírus Reviews and Research 12 2007mentioning
confidence: 86%
“…It is likely that the vaccine strains have been introduced into nature more than once. Over the years, several authors have confirmed the presence of infections in animals and humans by poxvirus, particularly in the Brazilian southeast (Mello et al 1960, Schatzmayr et al 2009a, 2009b, 2011Silva & Moraes 1962, Trindade et al 2003, Donatele et al 2007). It must be remembered that the smallpox vaccination campaign was discontinued in the country in the 1970s, which confirms that the vaccinialike virus is circulating in the country, a fact accepted in the international literature (Regnery 2007).…”
Section: Discussionmentioning
confidence: 96%
“…Damaso et al (2000) have shown that the virus, called Cantagalo (CTGV), isolated in municipalities with animals exhibiting vesicular/pustular disease is an Orthopoxvirus and that at the molecular level, this virus is very close to the sample vaccinia virus used in the past to prepare vaccines at the Instituto Oswaldo Cruz. Later, other authors confi rmed the circulation of similar viruses as a cause of infection in animals and humans, especially in the state of Rio de Janeiro and throughout southeastern Brazil (Costa et al 2007, Donatele et al 2007, Leite et al 2005, Nagasse-Sugahara et al 2004, Schatzmayr et al 2009a, Schatzmayr et al 2009b, Schatzmayr et al 2011, Trindade et al 2003, Trindade et al 2006, Trindade et al 2007. Th e movement of vaccinia virus has been confi rmed in the Brazilian territory and by reports in the international literature (Regnery 2007).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation